WHATSAPP MESSAGE EDUCATION IN STUDY: SOCIAL COGNITIVE THEORY TO PROMOTE PHYSICAL ACTIVITY AMONG RURAL PEOPLE WITH TYPE 2 DIABETES MELLITUS TAKALAR, INDONESIA - Herlina Jusuf 1, Zainuddin*2 , Benhard Latuminase 3, Amanda Adityaningrum4 (Chelonian Research Foundation, 2023)
Background: Social media (Whatsapp) is increasingly being used by older adults throughout the world. The question is whether they can be successfully incorporated into health programs to promote physical activity via WhatsApp applications in T2DM patients living in rural areas. The aim of this study was to measure the effect of an intervention via WhatsApp messages adapted from SCT theory to promote physical activity in T2DM patients living in rural areas. Method: Quantitative research design using Quasi-experiment. A non-probability sampling technique, namely purposive sampling, was carried out from May to August 2022 involving 60 T2DM patients. The intervention group received messages via educational WhatsApp messages or promotions on the importance of physical activity through SCT (Social Cognitive Theory) studies, namely (Cognitive (Knowledge), self-efficacy, and Physical Activity. Physical activity promotional messages were sent 3 messages per week for 6 weeks via the WhatsApp application so that a total of 18 messages would be sent during the intervention. Physical activity is only assessed at the beginning of week 7 to be followed up for 12 weeks with direct monitoring using the IPAQ (International Physical Activity Questionnaire) and the ESES (Exercise Self Efficacy) Questionnaire. Results: The PA program through SCT intervention with a mobile application showed a comparative change in reducing HbA1C between the intervention and control groups with an average score 8,766 ± 1,869 versus 9,743± 1,938 HbA1c mg/dl at 12 weeks. SCT intervention via mobile application (WhatsApp) causes changes in PA (MET (Metabolic Equivalents of Task), self-efficacy (p= large effect size on diastolic blood pressure (BP), Based on comparative analysis via Independent T Test significant decrease in (PA, HbA1C, self-efficacy) was found in the intervention group compared to the control group. Conclusion: The SCT Whatsapp message intervention via the mobile application (Group Whatsaap) increases physical activity, and can be included in health programs targeted for T2DM in rural areas. Keywords; Health promotion, SCT, mobile applications, physical activity, social media, WhatsApp